2005
DOI: 10.22621/cfn.v119i1.79
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Diets of Newfoundland Martens, <em>Martes americana atrata</em>

Abstract: We analyzed scats (n = 679) and stomach contents (n = 25) collected from 1980-2003 to assess the relative frequencies of food types utilized by Newfoundland Marten (Martes americana atrata) during summer and winter. Meadow Voles (Microtus pennsylvanicus) were the most prevalent food item occurring in 80% and 47.5% of samples from summer and winter, respectively. Apart from Snowshoe Hares (Lepus americana), which occurred in 28% of winter samples, all other food types occurred in <16% of samples during each sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…Additionally, in contrast to our study, Potvin et al (2000) assessed habitat use by martens during winter. Because habitat use and diet composition of martens are known to vary seasonally (Chapin et al 1997;Cumberland et al 2001;Gosse and Hearn 2005), it is likely that seasonality could influence the effect of habitat patchiness on occurrence of martens. Therefore, interspersion and juxtaposition likely have varying effects on occurrence of martens depending on season and forestry practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in contrast to our study, Potvin et al (2000) assessed habitat use by martens during winter. Because habitat use and diet composition of martens are known to vary seasonally (Chapin et al 1997;Cumberland et al 2001;Gosse and Hearn 2005), it is likely that seasonality could influence the effect of habitat patchiness on occurrence of martens. Therefore, interspersion and juxtaposition likely have varying effects on occurrence of martens depending on season and forestry practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, habitat use and diet composition of martens vary seasonally (Chapin et al 1997;Cumberland et al 2001;Gosse and Hearn 2005). Understanding habitat components beneficial to martens during summer is essential for deriving effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the positive effect of increased prey diversity and biomass for the Newfoundland Marten will be offset, to some degree, by a decrease in distribution and densities of Meadow Voles, which have been a historically important prey species (Bateman 1986;Drew 1995;Gosse and Hearn 2005;Tucker 1988). Further, indirect effects of the Red-backed Vole on Newfoundland Marten could occur as a result of the impact of this species on local Red Fox (Vulpes vulpes) populations.…”
Section: Discussionmentioning
confidence: 99%
“…Colgan (1987, 1990) suggested that, based on energetics, Marten in Ontario cannot survive exclusively on small rodents during late winter, and further, take small mammals opportunistically as they hunt for larger prey (i.e., Snowshoe Hare). Moreover, Gosse and Hearn (2005) reported that Snowshoe Hare provide >90% of the caloric intake of Newfoundland Marten in winter, the most energetically stressful period annually (Buskirk et al 1988). As cautioned by Fuller and Sievert (2001), the correlation between food and density-related demographic parameters is statistically broad, and many sitespecific factors (e.g., prey availability, habitat patchiness, habitat selection under foraging versus predationrisk trade-offs), influence home-range characteristics and carnivore density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation